A theoretical approach to understand the reaction dynamics for producing Technetium isotopes - Amit Chauhan (Nuclear Engineering and Technology, 2025)
Integrating theoretical research with experimental result is a way to understand reaction dynamics for the production of medically relevant radionuclides. The theoretical estimations of PACE4 and EMPIRE3.2.3 with GC, GSM and HF level densities are explored with the experimental data of the 9Be+89Y system to predict the optimum cross section for the production of 96,95.94g,m,93Tc and 92m,90Nb. The difference in theoretical and experimental excitation function of 95Tc of the 9Be+89Y at higher energy tail shows a signature of pre-equilibrium emissions during the thermalization of the compound nucleus. The variation of the isomeric ratio of 94Tc isotope with incident energy is extended to investigate the population of ground state and meta states of the concerned radionuclides.